Centering coastal communities’ diverse economic practices in the blue economy - Antonova, Anna S; Flannery, Wesley; Gómez, Sílvia; Gustavsson, Madeleine; Hadjimichael, Maria; Murtagh, Brendan; Ounanian, Kristen; Solnør, Sunniva; Steiro, Vida Maria Daae; Svels, Kristina (Pergamon Press, 2025)
Despite their stated commitment to sustainable economic development, blue economy and blue growth agendas have been criticized for replicating the same unlimited growth paradigm they purport to replace, disempowering local communities. By contrast, diverse economies literature advocates looking to communities’ practices to identify alternative, socially and environmentally grounded, economic possibilities. In line with that scholarship, this article calls for a re-envisioning of the blue economy through the eyes of coastal communities and their socio-ecological relations. We draw on local knowledge acquired from research we have conducted in six coastal communities across Europe – Burgas (Bulgaria); Connemara (Ireland); Træna (Norway); Åland (Finland); Cap de Creus (Spain); and Eastern Limassol (Cyprus). From mobilizing social enterprises and commoning practices to widening the blue economy’s goals to comprise environmental care and collective wellbeing, these communities’ economic practices focus not only on retaining value at the local level, but also on advancing societal and environmental goals. The article investigates the possibilities and challenges that these experiences suggest for the blue economy, raising questions about the potential of diverse blue economies.
Keywords: diverse economies; blue economy; coastal communities; commoning; economic geography